Water denitration over titania-supported Pt and Cu by combined photocatalytic and catalytic processes: Implications for hydrogen generation properties in a photocatalytic system. Issue 2 (April 2022) - Vasile, Anca; Papa, Florica; Bratan, Veronica; Munteanu, Cornel; Teodorescu, Mircea; Atkinson, Irina; Anastasescu, Mihai; Kawamoto, Daisuke; Negrila, Catalin; Ene, Cristian D.; Spataru, Tanta; Balint, Ioan
Abstract: The present work provides a new approach to the water denitration process and a facile strategy of catalyst preparation for the efficient hydrogen generation. The main focus of the research reported here was nitrate removal from aqueous solutions and simultaneous hydrogen generation under UV-Vis-light irradiation. This is a very important aspect in case of practical applications, eliminating the external source of hydrogen. Aiming to get a deeper understanding on the role of surface structures (size and shape of nanoparticles) towards the reduction mechanism and to establish basic principles for an efficient process, Pt-Cu/TiO2 and Pt-Cu/TiO2 modified with well-defined Pt nanoparticles were employed. The synthesized materials were characterized using various physicochemical techniques and tested comparatively for: (i) nitrate catalytic reduction by hydrogen (dark reaction) and (ii) nitrate photocatalytic reduction by in-situ generated solar hydrogen. In order to enhance overall denitration reaction by combined photocatalytic and catalytic processes, photo-generated charges and in-situ generated H2 as reducing agent were used. Improvement of catalytic performances of nitrate hydrogenation reaction (~100% NO3 ¯ conversion) related to intimate contact between Pt and Cu was obtained. The in-situ generated H2 by water splitting over the studied catalysts reduces efficiently NO3 ¯ ions. Enhanced photocatalytic activity toward solar H2 production by deposited well-defined Pt nanoparticles (~10 nm) was achieved. In order to make possible decontamination of polluted waters using in-situ generated H2 under light exposure, the future optimization of such photo-catalytic systems looks promising. Graphical Abstract: ga1 Highlights: Water denitration was carried out by combined photocatalytic and catalytic processes. The in-situ generated solar H2 by water splitting reduces efficiently nitrate ions. Deposition of well-defined Pt Np's (~10 nm) onto Pt-Cu/TiO2 enhances production of H2 .